Halogen adsorbents for the treatment of hydrocarbon process streams.

A sepiolite-attapulgite-carbonate adsorbent with controlled composition effectively addresses the challenge of high adsorption rates for both inorganic and organic halogens, mitigating corrosion and poisoning in hydrocarbon processing.

JP7602696B2Active Publication Date: 2024-12-18JGC CATALYSTS & CHEMICALS LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024525514
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-21
Filing Date
2023-12-18
Publication Date
2024-12-18
Estimated Expiration
2043-12-18

AI Technical Summary

Technical Problem

Conventional halogen adsorbents face challenges in achieving high adsorption rates for both inorganic and organic halogen compounds, leading to issues like equipment corrosion and catalyst poisoning.

Method used

An adsorbent composed of sepiolite, attapulgite, and a carbonate compound, with specific ratios of alkali and alkaline earth metal elements, optimized for high adsorption rates through controlled X-ray diffraction and infrared spectrum characteristics.

Benefits of technology

The adsorbent achieves enhanced adsorption rates for both inorganic and organic halogens, reducing corrosion and catalyst poisoning while minimizing organic halogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602696000002
    Figure 0007602696000002
  • Figure 0007602696000003
    Figure 0007602696000003
  • Figure 0007602696000004
    Figure 0007602696000004
Patent Text Reader

Abstract

Provided is an adsorbing agent that exhibits high adsorption rate for inorganic halogen compounds and organic halogen compounds. This adsorbing agent is for removing a halogen from a hydrocarbon-containing process stream, and contains sepiolite, attapulgite, and a carbonate compound. The carbonate compound contains an alkali metal element and / or an alkaline earth metal element. In an infrared spectrum obtained by measuring the adsorbing agent by using a Fourier transform infrared spectrophotometer, an absorption band having a local maximum value of (ACO3) at a wavelength of 1400-1500 cm-1 exists, and ACO3 is 0.180 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to halogen adsorbents for the treatment of hydrocarbon process streams. [Background technology]

[0002] In the field of petroleum refining, the hydrocarbons to be refined may contain chlorine compounds derived from the raw materials or catalytic treatment in the refining process. For example, used catalysts may be regenerated and reused, and chlorine compounds may be used for catalyst regeneration. When such regenerated catalysts are used, chlorine compounds may dissolve into the hydrocarbons. Both inorganic chlorine compounds and organic chlorine compounds are known as such chlorine compounds. If the hydrocarbons to be refined contain chlorine compounds, problems such as corrosion of the refining equipment by chlorine and poisoning of the catalysts used may occur.

[0003] As a method for removing chlorine compounds contained in hydrocarbons, a method for removing inorganic chlorine compounds and organic chlorine compounds using separate equipment is known, but this method has a problem of high cost. Therefore, chlorine compound adsorbents that can remove inorganic chlorine compounds and organic chlorine compounds simultaneously have attracted attention.

[0004] As such a chlorine compound adsorbent, an adsorbent mainly composed of zinc oxide has been conventionally known. For example, Patent Document 1 discloses a chlorine compound remover in which at least 10% by weight of an alkali metal or alkaline earth metal is added to a chlorine adsorbent composed of zinc oxide and a binder such as sepiolite, talc, or attapulgite (palygorskite).

[0005] Patent Document 2 discloses the use of a chloride absorbent that contains 10 to 80% by weight of a solid material that exhibits adsorption properties for organic chlorine compounds and 20 to 90% by weight of zinc oxide, and that absorbs 10 mg / L or more of organic chlorides in terms of chlorine.

[0006] However, adsorbents using zinc oxide generate zinc chloride, which has Lewis acidity, as the adsorption of chlorine compounds proceeds. It is known that on such materials exhibiting solid acidity, hydrocarbons in the fluid react with chlorine compounds to generate organic chlorine compounds, and the concentration of these compounds at the outlet of the adsorption tower becomes higher than the concentration at the inlet. Therefore, adsorbents for chlorine compounds that do not contain zinc oxide, as disclosed in Patent Documents 3 and 4, are also known. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2001-72984 A [Patent Document 2] JP 2008-184512 A [Patent Document 3] Patent Publication No. 2021-7937 [Patent Document 4] Special Publication No. 2018-523572 Summary of the Invention [Problem to be solved by the invention]

[0008] With conventional halogen adsorbents, it has been difficult to obtain an adsorbent that has a high adsorption rate for inorganic halogen compounds and organic halogen compounds.

[0009] Therefore, an object of the present invention is to provide an adsorbent that has a high adsorption rate for inorganic halogen compounds and organic halogen compounds. [Means for solving the problem]

[0010] The present inventors have discovered that the adsorbent contains sepiolite, attapulgite, and a carbonate compound, the carbonate compound containing at least one of an alkali metal element and an alkaline earth metal element, and that the adsorbent is measured using a Fourier transform infrared spectrophotometer and in the obtained infrared spectrum, the adsorbent has a wavelength of 1400 to 1500 cm -1 The maximum value (A CO3 ) has an absorption band, ACO3 The present inventors have found that the above problems can be solved by using an adsorbent having a β-adsorbent ratio of 0.180 or more, and have completed the present invention. Effect of the Invention

[0011] According to the present invention, it is possible to provide an adsorbent having a high adsorption rate for inorganic halogen compounds and organic halogen compounds. [Brief description of the drawings]

[0012] [Figure 1] 1 is an X-ray diffraction pattern of the adsorbent obtained by the method of Example 1. [Diagram 2] 1 is an X-ray diffraction pattern of the adsorbent obtained by the method of Example 2. [Diagram 3] 1 is an X-ray diffraction pattern of the adsorbent obtained by the method of Example 3. [Figure 4] 1 is an X-ray diffraction pattern of an adsorbent obtained by the method of Comparative Example 1. [Diagram 5] 1 is an X-ray diffraction pattern of an adsorbent obtained by the method of Comparative Example 2. [Figure 6] 1 is an X-ray diffraction pattern of an adsorbent obtained by the method of Comparative Example 3. [Figure 7] 1 is an X-ray diffraction pattern of an adsorbent obtained by the method of Comparative Example 4. [Figure 8] 1 is an X-ray diffraction pattern of an adsorbent obtained by the method of Comparative Example 5. [Figure 9] 1 is an X-ray diffraction pattern of an adsorbent obtained by the method of Comparative Example 6. [Figure 10] 1 is an infrared spectrum of the adsorbent obtained by the method of Example 1. [Figure 11] 1 is an infrared spectrum of the adsorbent obtained by the method of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention includes an invention related to an adsorbent for removing halogens (hereinafter, also referred to as "the adsorbent of the present invention"). In the present invention, the indication of "to" indicating a numerical range includes the upper and lower limits of the numerical range, for example, "X to Y" means X or more and Y or less. The adsorbent of the present invention will be described in detail below.

[0014] [Adsorbent of the present invention] The adsorbent of the present invention contains sepiolite, attapulgite, and a carbonate compound, the carbonate compound containing at least one of an alkali metal element and an alkaline earth metal element, and in the infrared spectrum obtained by measuring the adsorbent using a Fourier transform infrared spectrophotometer, -1 The maximum value (A CO3 ) has an absorption band, A CO3 is greater than or equal to 0.180.

[0015] The adsorbent of the present invention contains sepiolite. Sepiolite is one of the components of the adsorbent of the present invention and is an adsorbent for adsorbing halogen. Sepiolite is a type of clay mineral, and is a chain-like clay mineral different from layered clay minerals such as kaolin and talc, which are common clay minerals. The representative chemical structure of sepiolite is shown in the following formula (1). Mg4Si6O 15 (OH)2·6H2O (1)

[0016] Sepiolite is produced as a natural mineral, and its chemical composition may vary depending on its place of origin and refining method. However, even if the chemical composition is different, if a typical diffraction pattern of sepiolite is obtained in the X-ray diffraction of the adsorbent, it can be determined that the adsorbent contains sepiolite. In addition, even if the adsorbent uses sepiolite as a raw material, it can be determined that the adsorbent contains sepiolite. The mixed mass ratio of sepiolite in the adsorbent of the present invention is preferably in the range of 20 mass% or more and 50 mass% or less, more preferably in the range of 25 mass% or more and 50 mass% or less, and particularly preferably in the range of 30 mass% or more and 50 mass% or less, as a ratio to the total mass of the constituent components of the adsorbent. The adsorbent of the present invention containing a large amount of sepiolite has a high inorganic halogen adsorption rate.

[0017] The adsorbent of the present invention contains attapulgite. Attapulgite is one of the components of the adsorbent of the present invention, and is an adsorbent for adsorbing halogen. Attapulgite is a natural silicate mineral mainly composed of hydrated magnesium and aluminum silicate. As with the above-mentioned sepiolite, if a diffraction pattern derived from these can be confirmed in X-ray diffraction, it can be determined that the adsorbent contains attapulgite. In addition, even if the adsorbent uses attapulgite as a raw material, it can be determined that the adsorbent contains attapulgite. The mixed mass ratio of attapulgite in the adsorbent of the present invention is preferably in the range of 20 mass% or more and 50 mass% or less, more preferably in the range of 25 mass% or more and 50 mass% or less, and particularly preferably in the range of 30 mass% or more and 50 mass% or less, as a ratio to the total mass of the components of the adsorbent. The adsorbent of the present invention containing a large amount of attapulgite has a high organic halogen adsorption rate. In addition, the organic halogen generation rate is also likely to be slow.

[0018] The adsorbent of the present invention contains a carbonate compound, and the carbonate compound contains at least one of an alkali metal element and an alkaline earth metal element. The carbonate compound containing at least one of an alkali metal element and an alkaline earth metal element is one of the components of the adsorbent of the present invention, and is a component that suppresses the organic halogen generation rate. As with the above-mentioned sepiolite, if an X-ray diffraction pattern derived from the carbonate compound can be confirmed in X-ray diffraction, it can be determined that the adsorbent contains the carbonate compound. In addition, even if the adsorbent uses the carbonate compound as a raw material, it can be determined that the adsorbent contains the carbonate compound. However, this does not apply to adsorbents manufactured under conditions in which the carbonate compound decomposes, even if the carbonate compound is used as a raw material. The mixed mass ratio of the carbonate compound in the adsorbent of the present invention is preferably in the range of 1 mass% or more and 50 mass% or less, more preferably in the range of 5 mass% or more and 45 mass% or less, and particularly preferably in the range of 5 mass% or more and 40 mass% or less, as a ratio to the total mass of the components of the adsorbent. The adsorbent of the present invention, which contains both sepiolite and attapulgite and the carbonate compound in the above-mentioned range, has a high adsorption rate for inorganic halogens and organic halogens. In addition, the rate of organic halogen generation tends to be low. Furthermore, the carbonate compound is preferably at least one of magnesium carbonate and calcium carbonate, and more preferably calcium carbonate.

[0019] The adsorbent of the present invention is characterized in that, in the infrared spectrum obtained by measuring the adsorbent using a Fourier transform infrared spectrophotometer, the wavelength of the adsorbent is 1400 to 1500 cm -1 The maximum value (A CO3 ) has an absorption band, A CO3 The absorption band appearing in this wavelength region is an absorption band derived from carbonate radicals. The adsorbent of the present invention contains sepiolite, attapulgite and the carbonate compound, and has A CO3 When A is 0.180 or more, the adsorption rate of inorganic halogens and organic halogens is excellent. CO3is preferably in the range of 0.200 or more and 0.500 or less, and particularly preferably in the range of 0.220 or more and 0.400 or less. CO3 The adsorbent of the present invention having a fluorine content in the range described above has a high adsorption rate for inorganic halogens and organic halogens, and also tends to have a low generation rate for organic halogens.

[0020] The adsorbent of the present invention contains an inorganic compound having a hydroxyl group, and vinegar Spectral: 3500~3700cm -1 The maximum value (A OH ) has an absorption band, CO3 and A OH Ratio to (A CO3 / A OH ) is preferably in the range of 5 or more and 20 or less, more preferably in the range of 5 or more and 17 or less, and particularly preferably in the range of 5 or more and 14 or less. The absorption band appearing in this wavelength region is an absorption band derived from hydroxyl groups. Such hydroxyl groups are contained in, for example, the above-mentioned sepiolite, attapulgite, etc. In the present invention, by controlling the ratio between the maximum value of the absorption band derived from hydroxyl groups and the maximum value of the absorption band derived from carbonate groups within a certain range, an adsorbent having a high adsorption rate for inorganic halogens and organic halogens can be obtained.

[0021] The adsorbent of the present invention preferably contains calcium carbonate, and in the X-ray diffraction pattern, the ratio (A / B) of the intensity A of the peak appearing at 2θ=7.1°-7.6° to the intensity B of the peak appearing at 2θ=29°-30° is 0.120 or less. In the adsorbent of the present invention, the peak appearing at 2θ=7.1°-7.6° is a peak derived from sepiolite, and the peak appearing at 2θ=29°-30° is a peak derived from calcium carbonate (calcite). The adsorbent of the present invention contains sepiolite, attapulgite, and calcium carbonate, and by controlling the ratio (A / B) of these peak intensities within a specific range, the inorganic halogen adsorption capacity and organic halogen adsorption rate are high, and the organic halogen generation rate is slow. This ratio is not determined only by the mixing ratio of each component, but is affected by various factors such as the crystallinity and particle size of each component. This ratio is more preferably in the range of 0.001 to 0.120, particularly preferably in the range of 0.010 to 0.120, and most preferably in the range of 0.010 to 0.100.

[0022] The adsorbent of the present invention preferably contains calcium carbonate, and in the X-ray diffraction pattern, the ratio (C / B) of the intensity C of the peak appearing at 2θ=8.2° to 8.7° to the intensity B is 0.130 or less. In the adsorbent of the present invention, the peak appearing at 2θ=8.2° to 8.7° is a peak derived from attapulgite. The adsorbent of the present invention contains sepiolite, attapulgite, and calcium carbonate, and by controlling the ratio (C / B) of these peak intensities within a specific range, the inorganic halogen and organic halogen adsorption rate is increased and the organic halogen generation rate is decreased. This ratio is not determined only by the mixing ratio of each component, but is influenced by various factors such as the crystallinity and particle size of each component. This ratio is more preferably in the range of 0.001 to 0.130, and particularly preferably in the range of 0.010 to 0.130.

[0023] The adsorbent of the present invention may contain, as one of its constituent components, a component other than sepiolite, attapulgite, and the carbonate compound. For example, the adsorbent may contain silica, alumina, zeolite, clay minerals, organic binders, etc. as a pore-forming component, diluent component, or binder component. The mixed mass ratio of these components is preferably in the range of 10 mass% or more and 50 mass% or less, more preferably in the range of 20 mass% or more and 40 mass% or less, as a ratio to the total mass of the constituent components of the adsorbent.

[0024] The calcium (Ca) content of the adsorbent of the present invention is preferably in the range of 1 mass % or more and 50 mass % or less, more preferably in the range of 5 mass % or more and 40 mass % or less, and particularly preferably in the range of 10 mass % or more and 40 mass % or less, calculated as CaO, based on the total amount of the adsorbent. The calcium contained in the adsorbent of the present invention is mainly derived from calcium that can be contained in calcium carbonate, sepiolite, and attapulgite.

[0025] The magnesium (Mg) content of the adsorbent of the present invention is preferably in the range of 1 mass % or more and 25 mass % or less, more preferably in the range of 3 mass % or more and 25 mass % or less, and particularly preferably in the range of 8 mass % or more and 15 mass % or less, calculated as MgO, relative to the total amount of the adsorbent. The magnesium contained in the adsorbent of the present invention is mainly derived from magnesium contained in sepiolite, attapulgite and magnesium carbonate.

[0026] The silicon (Si) content of the adsorbent of the present invention is preferably in the range of 20% by mass or more and 70% by mass or less, more preferably 30% by mass or more and 70% by mass or less, calculated as SiO2, based on the total amount of the adsorbent. The silicon contained in the adsorbent of the present invention is mainly derived from the silicon contained in sepiolite and attapulgite. In addition, when silica is used as a binder component, it is also derived from this.

[0027] The aluminum (Al) content of the adsorbent of the present invention is preferably in the range of 1 mass % or more and 40 mass % or less, and more preferably in the range of 1 mass % or more and 20 mass % or less, in terms of Al2O3, based on the total amount of the adsorbent. The aluminum contained in the adsorbent of the present invention is considered to be a binder component or an impurity contained in sepiolite and attapulgite.

[0028] The zinc (Zn) content of the adsorbent of the present invention is preferably 10 mass% or less, more preferably 1 mass% or less, and particularly preferably 0.1 mass% or less, calculated as ZnO, based on the total amount of the adsorbent. When the adsorbent of the present invention contains zinc oxide, the rate of organic halogen generation tends to increase. Therefore, the zinc content is preferably low.

[0029] The average pore size of the adsorbent of the present invention is preferably in the range of 10 nm to 50 nm, more preferably in the range of 10 nm to 40 nm, and particularly preferably in the range of 10 nm to 30 nm. The adsorbent of the present invention having an average pore size in the above-mentioned range is easy to diffuse hydrocarbons in a hydrocarbon-containing process stream. This makes it easy for the adsorbent of the present invention to adsorb halogens contained in the hydrocarbons. The average pore size in the present invention refers to the average pore size in the pore distribution obtained from the adsorption isotherm obtained by the nitrogen adsorption method.

[0030] The pore volume of the adsorbent of the present invention is preferably in the range of 0.20 mL / g or more and 1.00 mL / g or less, more preferably in the range of 0.25 mL / g or more and 0.90 mL / g or less, and particularly preferably in the range of 0.30 mL / g or more and 0.80 mL / g or less. The adsorbent of the present invention having a pore volume in the above-mentioned range is more likely to diffuse hydrocarbons into the inside of the adsorbent in a hydrocarbon-containing process stream. This makes it easier for halogens contained in the hydrocarbons to be adsorbed by the adsorbent of the present invention. The pore volume in the present invention refers to the average pore diameter in the pore distribution obtained from the adsorption isotherm obtained by the nitrogen adsorption method.

[0031] The specific surface area of ​​the adsorbent of the present invention is 40 m 2 / g or more, 250m 2 / g or less, and 2 / g or more, 225m 2 / g or less, and more preferably 120m 2 / g or more, 200m 2 It is particularly preferred that the specific surface area is in the range of 0.1 to 1.0 μm / g or less. The adsorbent of the present invention having a specific surface area in the above-mentioned range allows hydrocarbons to easily diffuse into the adsorbent in a hydrocarbon-containing process stream. This makes it easier for halogens contained in the hydrocarbons to be adsorbed by the adsorbent of the present invention. The specific surface area in the present invention refers to the specific surface area determined by the BET one-point method.

[0032] The bulk density of the adsorbent of the present invention is preferably in the range of 0.30 g / mL or more and 1.10 g / mL or less, more preferably in the range of 0.35 g / mL or more and 0.90 g / mL or less. The adsorbent of the present invention has an excellent adsorption speed for inorganic halogen compounds and organic halogen compounds, so that it can efficiently adsorb halogens even if the bulk density is low.

[0033] The shape of the adsorbent of the present invention may be spherical, columnar (including cylindrical and four-lobe) or similar. The size (the minimum length of the outer shape of the adsorbent) is preferably in the range of 0.5 mm to 6 mm. If the size of the adsorbent is small, the contact area between the adsorbent and the hydrocarbon increases, and the adsorption rate of halogen contained in the hydrocarbon increases.

[0034] The adsorbent of the present invention can remove halogens contained in various media, and can more efficiently remove halogens contained in hydrocarbon process streams. The aforementioned media can be liquid or gas. The adsorbent of the present invention can more efficiently remove halogens even from liquids, which tend to have a lower halogen removal efficiency than gases. The adsorbent of the present invention can particularly efficiently remove halogens contained in liquid carbonization process streams. This is due to the low organic halogen generation ability of the adsorbent of the present invention.

[0035] [Method of producing the adsorbent of the present invention] The adsorbent of the present invention can be prepared, for example, by using a production method including the following steps (1) to (3). (1) A step of preparing a molded precursor by mixing sepiolite, attapulgite, a carbonate compound containing at least one of an alkali metal element and an alkaline earth metal element, and a solvent. (2) A molding step of forming the shaped precursor into pellets to obtain an adsorbent precursor. (3) A drying step of drying the adsorbent precursor at a temperature of 350° C. or less to obtain an adsorbent.

[0036] Hereinafter, the method for producing the adsorbent of the present invention will be described in detail by taking this production method as an example, but the production method for the adsorbent of the present invention is not limited to this production method.

[0037] [(1) Molding precursor preparation process] The manufacturing method includes a molded precursor preparation step of mixing sepiolite, attapulgite, a carbonate compound containing at least one of an alkali metal element and an alkaline earth metal element, and a solvent to prepare a molded precursor. In this step, a clay-like kneaded product containing each of the components of the adsorbent of the present invention is prepared.

[0038] The mixing ratio of sepiolite in this step is preferably in the range of 20% by mass or more and 50% by mass or less, more preferably in the range of 25% by mass or more and 50% by mass or less, and particularly preferably in the range of 30% by mass or more and 50% by mass or less, based on the total amount of solids excluding the solvent. The mixing ratio of attapulgite in this step is preferably in the range of 20% by mass or more and 50% by mass or less, more preferably in the range of 25% by mass or more and 50% by mass or less, and particularly preferably in the range of 30% by mass or more and 50% by mass or less, based on the total amount of solids excluding the solvent. The mixing ratio of calcium carbonate in this step is preferably in the range of 5% by mass or more and 50% by mass or less, more preferably in the range of 5% by mass or more and 45% by mass or less, and particularly preferably in the range of 5% by mass or more and 40% by mass or less, based on the total amount of solids excluding the solvent. The sepiolite, attapulgite and carbonate compound in this step may be commercially available products or synthetic products.

[0039] In this step, a component other than sepiolite, attapulgite, and the carbonate compound can be mixed as one of the constituent components. For example, silica, alumina, zeolite, clay minerals, organic binders, etc. may be mixed as a pore-forming component, diluent component, or binder component. The mixing ratio of these components is preferably in the range of 10% by mass or more and 50% by mass or less, and more preferably in the range of 20% by mass or more and 40% by mass or less, based on the total amount of solids excluding the solvent.

[0040] In this step, in addition to the aforementioned components, a solvent is mixed. This solvent is a component for fixing the aforementioned components together to form a precursor suitable for molding. In this step, both inorganic and organic solvents can be used as the solvent, and it is preferable to use an inorganic solvent, and it is more preferable to use water. The mixing ratio of the solvent varies depending on the properties of the aforementioned components, and it is difficult to determine a preferred range, but it is preferable to mix in a range of 10% by mass or more and 70% by mass or less with respect to the total amount of the molding precursor. If the amount of solvent added is small, the aforementioned components tend to stick together and become granular, and such a molding precursor can be suitably used as a precursor for tablet molding. Also, if the amount of solvent added is large, the aforementioned components tend to stick together and become clay-like, and such a molding precursor can be suitably used as a precursor for extrusion molding.

[0041] In this step, the components can be mixed by a conventional method. For example, they can be mixed using a high-speed mixer, a mill, or the like. They can also be mixed using a kneader. These mixing methods can be appropriately selected so as to match the production process.

[0042] [(2) Molding process] In this step, the molded precursor obtained in the above step can be molded using a conventional method. For example, it can be molded into pellets using tablet molding, extrusion molding, etc. When using tablet molding, it is recommended to use a method in which the granular molded precursor is set in a tablet molding machine and a certain pressure is applied. The shape of the adsorbent finally obtained can be determined by the shape of the cylinder used at this time. In addition, when using extrusion molding, it is recommended to use a single-axis auger type extruder or a disk pelleter for the clay-like molded precursor. The shape of the adsorbent finally obtained can be determined by the shape of the die used at this time.

[0043] [(3) Drying process] In this step, the adsorbent precursor obtained in the above step can be dried using a conventionally known method. For example, air drying, heat drying, reduced pressure drying, or a combination of these methods can be used. The drying temperature is preferably 300°C or less, more preferably 250°C or less. This is to prevent the properties of each component contained in the adsorbent precursor from changing due to heat. In particular, if the temperature is high, the carbonate compound may decompose, or the structure of sepiolite or attapulgite may change.

[0044] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0045] [Measurement method or evaluation method] The various measurements and evaluations were carried out as follows.

[0046] [1]FT-IR measurement (ATR method) The adsorbents obtained in the respective Examples were pulverized into powder form, and the infrared spectrum of each adsorbent was measured under the following conditions. <Condition> Model name: FT / IR-6100typeA Accessory name: ATR PRO470-H Incident angle: 45 degrees Light source: Standard light source included with the device Detector: TGS Number of times: 16 Resolution: 4 cm -1 Zero filling: On Apodization: Cosine Gain: Auto (32) Aperture: Auto (7.1 mm) Scan speed: Auto (2 mm / sec) Filter: Auto (10000 Hz)

[0047] [2] X-ray diffraction measurements The adsorbents obtained in the respective Examples were pulverized into powder form, and then subjected to powder X-ray diffraction measurement under the following conditions. <Condition> X-ray diffraction equipment: MiniFlex600 (Rigaku Corporation) Radiation source: Cu-Kα radiation Acceleration voltage, current: 40 kV, 15 mA Receiving slit: 13mm Scan speed: 5.0° / min Step width: 0.01° Measurement range (2θ): 5~90°

[0048] [3] Composition analysis (Ca, Mg, Si, Al) The adsorbents obtained in each example were pulverized into powder, and then the samples were placed in a pressure molding ring and pressure molded for 3 minutes at a molding pressure of 30 MPa. The molded samples were placed in an X-ray fluorescence analyzer (ZSX100e, manufactured by Rigaku Corporation) and measured by order (semi-quantitative) analysis.

[0049] [4] Pore distribution About 3 g of the adsorbent obtained in each Example was collected in a porcelain crucible, and after heat treatment at a temperature of 500°C for 1 hour, it was placed in a desiccator and cooled to room temperature to obtain a measurement sample. Using this measurement sample, the pore distribution of the adsorbent was measured under the following conditions. The pore distribution was measured under the following conditions. Pore ​​size distribution measuring device: PM-33GT1LP (QUANTA CROME) Sample volume: 3g Pore ​​size measurement range: 5nm~5000nm Contact angle of mercury: 150° Surface tension of mercury: 480 dyn / cm From the obtained pore distribution, the total volume of pores having a pore diameter in the range of 5 nm to 5000 nm was determined as the pore volume.

[0050] [5] Specific surface area <Method of measuring the surface area (specific surface area N2) of a catalyst using the single-point BET method for nitrogen adsorption / desorption measurement> Approximately 30 mL of the adsorbent obtained in each Example was placed in a porcelain crucible (B-2 type), heated at 110°C for 2 hours, and then cooled to room temperature in a desiccator to obtain a sample for measurement. Next, 1 g of this sample was taken and the specific surface area (m 2 / g) was measured by the BET method.

[0051] [6] Bulk density 50 g of the adsorbent obtained in each Example was dropped under its own weight from the upper opening of a 250 ml measuring cylinder to fill it, and the volume (V1) was measured when the top of the packed bed was made horizontal, and calculated using the following formula. Bulk density = 50 / V1 [g / mL]

[0052] [7] Halogen adsorption test (Inorganic halogen adsorption rate constant) The adsorbents obtained in each example were packed in a reaction tube so that the bed height was 20 mm, and attached to an adsorption test device. The reaction tube was pretreated at 150°C for 1 hour under nitrogen flow, and then cooled to room temperature. Then, xylene containing 500 ppm of hydrogen chloride was passed through at a rate of 1 ml / min. The flowing liquid at the inlet and outlet of the reaction tube was sampled at predetermined intervals, and the chlorine concentration was measured using a trace chlorine analyzer (TCL-2100V, manufactured by Nitto Seiko Analytech Co., Ltd.). The inorganic halogen adsorption rate constant was calculated from the difference between the chlorine concentrations at the inlet and outlet and the residence time of the flowing liquid in the adsorbent. The flow in this test was continued for 60 hours or more, and an adsorbent with saturated adsorption of inorganic halogen was obtained.

[0053] (Organic halogen adsorption rate constant) The adsorbents obtained in each example were packed in a reaction tube with a bed height of 50 mm and attached to an adsorption test device. The reaction tube was pretreated at 150°C for 1 hour under nitrogen flow, and then cooled to room temperature. Then, reformate (reformed naphtha) containing 0.5 ppm of organic chlorine compounds was passed through at a rate of 0.2 ml / min. The flowing liquid at the inlet and outlet of the reaction tube was sampled at predetermined intervals, and the chlorine concentration was measured using a trace chlorine analyzer (TCL-2100V, manufactured by Nitto Seiko Analytech Co., Ltd.). The organic halogen adsorption rate constant was calculated from the difference between the chlorine concentrations at the inlet and outlet and the flowing liquid residence time in the adsorbent.

[0054] (Organohalogen formation rate constant) The adsorbent saturated with inorganic halogens was packed closely in a reaction tube to a bed height of 10 mm, and attached to an adsorption test device. Then, xylene containing 10% hexene was passed through at a rate of 0.1 ml / min. The flowing liquid at the inlet and outlet of the reaction tube was sampled at predetermined intervals, and the chlorine concentration was measured using a trace chlorine analyzer (TCL-2100V, manufactured by Nitto Seiko Analytech Co., Ltd.). The organic halogen generation rate constant was calculated from the increase in the chlorine concentration at the inlet and outlet and the residence time of the flowing liquid in the adsorbent.

[0055] [Example 1] 177 g of sepiolite powder (purchased by IMV NEVADA, product name: THERMOGEL), 167 g of attapulgite powder (purchased by Active Minerals, product name: Min-U-Gel-200), 64.3 g of calcium carbonate (purchased by Konoshima Chemical, product name: light calcium carbonate), and 240 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. This molding precursor was molded in an extrusion molding machine to obtain an adsorbent precursor. This adsorbent precursor was dried in an electric dryer at 120°C for 12 hours and further dried at 200°C for 3 hours to obtain a cylindrical adsorbent with a diameter of 1.2 to 1.3 mmφ and a height of 3 to 5 mm. The above-mentioned measurements and evaluations of [1] to [7] were performed on this adsorbent. The results are shown in Table 1. The X-ray diffraction pattern of Example 1 obtained by the measurement of [2] is shown in FIG. 1. Furthermore, the infrared spectrum of Example 1 obtained by the measurement of [1] is shown in FIG. 10.

[0056] [Example 2] 141 g of sepiolite powder (purchased from IMV NEVADA, product name: THERMOGEL), 133 g of attapulgite powder (purchased from Active Minerals, product name: Min-U-Gel-200), 161 g of calcium carbonate (purchased from Konoshima Chemical, product name: light calcium carbonate), and 210 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were carried out in the same manner as in Example 1. The X-ray diffraction pattern of Example 2 is shown in FIG. 2, and the results are shown in Table 1.

[0057] [Example 3: Use of silica binder] 125 g of sepiolite powder (purchased by IMV NEVADA, product name: THERMOGEL), 117 g of attapulgite powder (purchased by Active Minerals, product name: Min-U-Gel-200), 42.8 g of calcium carbonate (purchased by Konoshima Chemical, product name: light calcium carbonate), 99.1 g of amorphous silica (purchased by Oriental Silicas Corporation, product name: Toxil 928) as a binder component, and 450 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were performed in the same manner as in Example 1. The X-ray diffraction pattern of Example 3 is shown in FIG. 3, and the results are shown in Table 1.

[0058] [Example 4: Use of silica binder] 121 g of sepiolite powder (purchased from IMV NEVADA, product name: THERMOGEL), 114 g of attapulgite powder (purchased from Active Minerals, product name: Min-U-Gel-200), 54 g of calcium carbonate (purchased from Konoshima Chemical, product name: light calcium carbonate), 99 g of amorphous silica (purchased from Oriental Silicas Corporation, product name: Toxil 928) as a binder component, and 510 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0059] [Example 5: Use of alumina binder] An adsorbent was obtained in the same manner as in Example 4, except that 129 g of alumina (purchased from JGC Catalysts and Chemicals, product name: AP-1) was used as the binder component. The obtained adsorbent was evaluated in the same manner as in Example 1. The results are shown in Table 1.

[0060] [Example 6: Use of magnesium carbonate] 181 g of sepiolite powder (purchased from IMV NEVADA, product name: THERMOGEL), 171 g of attapulgite powder (purchased from Active Minerals, product name: Min-U-Gel-200), 71 g of magnesium carbonate (purchased from Fujifilm Wako Pure Chemical Industries, product name: Basic magnesium carbonate Wako Grade 1) and 220 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0061] [Comparative Example 1: No calcium carbonate] 201 g of sepiolite powder (purchased by IMV NEVADA, product name: THERMOGEL), 190 g of attapulgite powder (purchased by Active Minerals, product name: Min-U-Gel-200), and 260 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were carried out in the same manner as in Example 1. The X-ray diffraction pattern of Comparative Example 1 is shown in FIG. 4, and the results are shown in Table 1. The infrared spectrum of Comparative Example 1 obtained by the measurement in [1] is shown in FIG. 11.

[0062] [Comparative Example 2: No attapulgite] 354 g of sepiolite powder (purchased by IMV NEVADA, product name: THERMOGEL), 64.3 g of calcium carbonate (purchased by Konoshima Chemical, product name: light calcium carbonate), and 220 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were carried out in the same manner as in Example 1. The X-ray diffraction pattern of Comparative Example 2 is shown in FIG. 5, and the results are shown in Table 1.

[0063] [Comparative Example 3: Sepiolite only] 403 g of sepiolite powder (purchased from IMV NEVADA, product name: THERMOGEL) and 200 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were carried out in the same manner as in Example 1. The X-ray diffraction pattern of Comparative Example 3 is shown in FIG. 6, and the results are shown in Table 1.

[0064] [Comparative Example 4: No sepiolite] 334 g of attapulgite powder (purchased from Active Minerals, product name: Min-U-Gel-200), 64.3 g of calcium carbonate (purchased from Konoshima Chemical, product name: light calcium carbonate), and 290 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were carried out in the same manner as in Example 1. The X-ray diffraction pattern of Comparative Example 4 is shown in FIG. 7, and the results are shown in Table 1.

[0065] [Comparative Example 5: Attapulgite only] 379 g of attapulgite powder (purchased from Active Minerals, product name: Min-U-Gel-200) and 300 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were carried out in the same manner as in Example 1. The X-ray diffraction pattern of Comparative Example 5 is shown in FIG. 8, and the results are shown in Table 1.

[0066] [Comparative Example 6: Calcium hydroxide] 177 g of sepiolite powder (purchased from IMV NEVADA, product name: THERMOGEL), 167 g of attapulgite powder (purchased from Active Minerals, product name: Min-U-Gel-200), 50.1 g of calcium hydroxide (purchased from Fujifilm Wako Pure Chemical Industries, product name: calcium hydroxide), and 380 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were performed in the same manner as in Example 1. The X-ray diffraction pattern of Comparative Example 6 is shown in FIG. 9, and the results are shown in Table 1.

[0067] [Comparative Example 7: No carbonate compound] 141 g of sepiolite powder (purchased by IMV NEVADA, product name: THERMOGEL), 133 g of attapulgite powder (purchased by Active Minerals, product name: Min-U-Gel-200), 129 g of amorphous silica (purchased by Oriental Silicas Corporation, product name: Toxil 928) as a binder component, and 450 g of ion-exchanged water were mixed in a kneader to obtain a clay-like molding precursor. The subsequent steps and evaluations were performed in the same manner as in Example 1.

[0068] [Table 1]

Claims

1. 1. An adsorbent for removing halogens from a hydrocarbon-containing process stream, comprising: Contains sepiolite, attapulgite and carbonate compounds. the carbonate compound contains at least one of an alkali metal element and an alkaline earth metal element, The adsorbent is measured using a Fourier transform infrared spectrophotometer, and in the obtained infrared spectrum, the wavelength is 1400 to 1500 cm -1 The maximum value (A CO3 ) has an absorption band, A CO3 is 0.180 or more, Adsorbent.

2. The inorganic compound contains a hydroxyl group, and the infrared spectrum shows a wavelength of 3500 to 3700 cm -1 The maximum value (A OH ) has an absorption band, CO3 and A OH Ratio to (A CO3 / A OH 2. The adsorbent according to claim 1, wherein the molecular weight of the adsorbent is 5 or more and 20 or less.

3. The sorbent of claim 2, wherein the carbonate compound is calcium carbonate.

4. The adsorbent according to claim 3, wherein in an X-ray diffraction pattern, a ratio (A / B) of a peak intensity A appearing at 2θ=7.1° to 7.6° to a peak intensity B appearing at 2θ=29° to 30° is 0.120 or less.

5. 5. The adsorbent according to claim 4, wherein in an X-ray diffraction pattern, the ratio (C / B) of the intensity C of a peak appearing at 2θ=8.2° to 8.7° to the intensity B is 0.130 or less.

6. The adsorbent according to claim 5, having an average pore size in the range of 10 nm or more and 50 nm or less in a pore size distribution measured by mercury intrusion porosimetry.

7. The adsorbent according to claim 6, having a pore volume in the range of 0.30 mL / g or more and 1.10 mL / g or less in a pore distribution measured by mercury intrusion porosimetry.

8. The adsorbent according to claim 7, having a Ca content, calculated as CaO, in the range of 5 mass % to 40 mass % relative to the total mass of the adsorbent.

9. The adsorbent according to claim 8, having a Mg content, calculated as MgO, in the range of 1 mass % or more and 25 mass % or less with respect to the total mass of the adsorbent.

10. The Si content is SiO 2 The adsorbent according to claim 9, wherein the adsorbent content is in the range of 20 mass% or more and 70 mass% or less in terms of the converted amount.

Citation Information

Patent Citations

  • Organic modified particle attapulgite adsorbent and preparing method thereof

    CN106925240A

  • Basic composite porous body and its production

    JP1997221373A

  • Chlorine compound remover and method for removing chlorine compound from hydrocarbon fluid by using same

    JP2001072984A

  • Organopolysiloxane-chainlike clay mineral complex and its use

    JP2002338236A

  • Carbonated hardened body

    JP2005187324A